Protective effect of Schizandrin B against damage of UVB irradiated skin cells depend on inhibition of inflammatory pathways. Issue 1 (2nd January 2017) - Gao, Chenguang; Chen, Hong; Niu, Cong; Hu, Jie; Cao, Bo
ABSTRACT: Schizandrin B is extracted from Schisandra chinensis (Turcz.) Baill. This study evaluated the photoprotective effect of Schizandrin B on oxidative stress injury of the skin caused by UVB-irradiation and the molecular mechanism of the photoprotective effect of Schizandrin B, and we firstly found that Schizandrin B could block Cox-2, IL-6 and IL-18 signal pathway to protect damage of skin cells given by UVB-irradiation. In the research, we found that Schizandrin B can attenuate the UVB-induced toxicity on keratinocytes and dermal fibroblasts in human body, and can outstandingly eliminated intracellular ROS produced by UVB-irradiation. These results demonstrate that Schizandrin B can regulate the function of decreasing intracellular SOD's activity and increasing the expression level of MDA in HaCaT cells result from the guidance of UVB, and it markedly reduced the production of inflammatory factors such as Cox-2, IL-6 or IL-18, decreased the expression level of MMP-1, and interdicted degradation process of collagens in UVB-radiated cells. Therefore, skin keratinocytes can be effectively protected from UVB-radiated damage by Schizandrin B, and UVB-irradiation caused inflammatory responses can be inhibited by attenuating process of ROS generating.